The representation of veiled versus non-veiled women in advertising:a comparative analysis of local and western brands' Instagram posts - El-Banna, Doaa (AUC Knowledge Fountain, 2020)
This study utilizes content analysis techniques to examine if there is a significant difference in the representation of veiled versus non-veiled women in both local and western brand’s Instagram posts. The brand’s Instagram posts are all essentially created for the purposes of advertising and promoting products and/or services. The content analysis is based on Erving Goffman’s “gender analysis” model, testing the following five categories: Feminine Touch, Ritualization of Subordination, Licensed Withdrawal, Body Display, and Independence. Only one of the five categories showed a significant difference in the representation of veiled versus non-veiled women in brands’ Instagram posts. Findings revealed that there is a significant difference in “Body Display” between veiled versus non-veiled women in brands’ Instagram posts. Interestingly, the study analysis showed that the significant difference in “Body Display” between veiled and non-veiled women appeared only in western brand’s Instagram posts, while local brands’ posts showed no difference in the representation of veiled versus non-veiled women along the five categories tested.